METHODS FOR DEVELOPING MUSICAL AND ARTISTIC TASTE - Khodjiyeva, Dilfuza (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This thesis examines the issues of forming and developing the musical-artistic taste of students in piano classes at children’s music and art schools. Based on the analysis of scientific and theoretical sources, the significance of using innovative pedagogical technologies and interactive methods in the modern educational process is highlighted. The study also identifies problems in transitioning students from mechanical performance to expressive and artistically meaningful interpretation, and proposes effective methods aimed at developing musical thinking, aesthetic outlook, and performance skills.